A Huge Cystic Retroperitoneal Lymphangioma Presenting with Back Pain - Mahir Gachabayov; Kubach Kubachev; Elbrus Abdullaev; Valentin Babyshin; Dmitriy Neronov; Abakar Abdullaev (Case Reports in Medicine)
Retroperitoneal lymphangioma is a rare location and type of benign abdominal tumors. The clinical presentation of this rare disease is nonspecific, ranging from abdominal distention to sepsis. Here we present a 73-year-old female patient with 3-month history of back pain. USG and CT revealed a huge cystic mass which was surgically excised and appeared to be lymphangioma on histopathology.